(untitled) (Issues in Social and Environmental Accounting (ISEA), 2014)
When studying fishing activities in south Mediterranean, particularly in Algeria, we face the particular case of coastal territory. The high dependence of human activities on marine territo ries and their resources is always related to the high level of conflicts, between fishing actors and other stakeholders, generated by some conservation projects. The aim of this paper is to highlight and illustrate the approach of MPAs (Marine Protected Areas) governance and their role in conserving biodiversity, in order to clarify their economic, social and environmental impacts on human activities such as fishing. This paper defends the flowing thesis: in the long term, protection could reduce conflicts, contribute to sustainable management of fisheries and improve the welfare of fishers’ community.